Fabrication of conductive silver paste recovered from leaching of waste catalyst using hydrochloric acid. Issue 16 (28th March 2022) - Lee, Suhyeon; Frimpong, Brakowaa; Abbey, Stanley; Moon, Yoon Sil; Yoo, Kyoungkeun; Oh, Young-Min; Kim, Soo-Kyung; Kim, Sang-Joon; Oh, Min-Wook
Abstract : The silver paste was synthesized by a hydrometallurgical method from waste catalyst. Abstract : Transition metal compounds based on silver (Ag) and palladium (Pd) are extensively used as catalysts in the petrochemical industries. The catalytic activities of Ag and Pd decrease over time and hence need to be discarded. The recovery of elements like Ag from waste catalyst is essential because of its limited availability and cost, and it is environmentally beneficial with regards to recycling. In this study, Pd and Ag were leached from waste catalyst providing an alternative source suitable for a Ag paste electrode. Through an efficient reduction process, AgCl particles were obtained which serve as a precursor to synthesize Ag using ammonia as the solvent. The obtained Ag was fabricated to Ag paste by using mixed dispersion and solvent. The electrical resistivity of the Ag paste was recorded as 6.14 μΩ cm at 417 °C in a hydrogen atmosphere.